Heterogeneity of b lymphocyte differentiation in severe combined immunodeficiency disease. - Pahwa, S G (1980)
Pokeweed mitogen-induced B lymphocyte differentiation in vitro into antibody secreting plaque-forming cells (PFC) was investigated in nine patients with severe combined immunodeficiency having variable proportions of circulating B lymphocytes. When cultured by themselves, the peripheral blood mononuclear cells did not respond to stimulation with pokeweed mitogen in any patient. In the presence of irradiated allogeneic T cells as helpers, however, PFC responses were elicited in lymphocyte cultures from peripheral blood and/or bone marrow in some patients. In one of these patients, results of allogeneic co-culture experiments were suggestive of genetically restricted suppressor cells. In a single patient with deficiency of the enzyme adenosine deaminase, PFC were generated in bone marrow lymphocyte cultures only when they were supplemented with exogenous adenosine deaminase and allogeneic helper cells. A parallel study of T lymphocyte differentiation in vitro performed in fractionated bone marrow cells was suggestive of arrested differentiation at different steps along the differentiation pathway. In two patients with evidence of functional B cell precursors, deficiencies of helper T cell function could be attributed to differentiation defects at the level of the stem cells in one and the thymus in the other. The findings reported here further substantiate the heterogeneity of the severe combined immunodeficiency disease syndromes.